Forehead Flap for Facial Defects Reconstruction: Case Series and Review of The Literature - Handoko, Tan Margaretha Heidina; Samuel, Darryl; Victe, Dona Christin; Yolla, Zulaekha; Sitorus, Gina Yunita Joice (Jurnal Plastik Rekonstruksi, 2023)
Introduction: Forehead flap is one of the oldest techniques for reconstruction of the facial defects. Throughout the years, various advances in technologies and surgical techniques are continuously developing. Despite the ongoing advances in technology, forehead flap may be a simpler and useful alternative for facial defects.Method: This study was a retrospective case series of four patients presented to Dr. Kariadi Central-General Hospital during 2021-2022 with facial defects undergoing reconstruction with forehead flap. Case report based on the medical and surgical records.Result: All patients underwent reconstruction surgery in 2 stages. The first stage was flap elevation and transfer, and the second surgery was flap division and inset weeks later. All patients had overall good outcomes.Conclusion: Forehead flap is technically simple to perform, easy to master and provides good outcomes. In cases of free flap loss, a forehead flap can be used as a Plan B. Therefore, forehead flap is a reliable option for facial defect reconstruction and should be mastered especially by general plastic surgeons.